Perlindungan Hukum Bagi Kreditur Bank pada Perjanjian Kawin dalam Perkawinan Campuran - Kadek Megah Bintaranny; I Nyoman Putu Budiartha; I Wayan Arthanaya (Jurnal Interpretasi Hukum, 2020)
The problem faced by the couple of a mixed marriage in Indonesia is that there are provisions in Indonesian law regarding the incorporating of assets immediately into joint property after the marriage. But on the other hand, there are laws regulating that foreigners may not own property rights in Indonesia, so joint property involving a number of properties in the form of movable or immovable property will be impossible for foreigners to own. This study examines two issues: the legal protection for third party, the bank creditors relating to the status/property status of a married couple in mixed marriages in a marriage agreement and the legal consequences of non-performing loans related to the couple’s property if they commit defaults. To uncover these two matters, the study was conducted using the normative legal research method. The results show that creditors are protected in a preventive and repressive manner. Legal consequences for husband or wife property for bank creditors if the debtor is bound in the mixed marriage defaults depend on the form of the marriage agreement made. A husband or wife who is an Indonesian citizen as a debtor is permitted to guarantee the material security of his assets freely and can be taken as collateral for repayment by the bank’s creditors if the debtor is in default.